Metastatic lesions in the mandible: a case series and literature review. (24th October 2020) - Rovira‐Wilde, A.; McKernon, S.L.; Balmer, C.
Abstract: The clinical presentation, diagnostic challenges and management of three cases of metastatic lesions in the mandible are presented. The clinical records, investigations and histopathological reports of three patients presenting with metastatic jaw lesions were reviewed. Patients were all female, aged 41, 59 and 61 years. Clinical presentation in all cases included intra‐oral swelling, oral pain, paraesthesia and dysesthesia related to the inferior alveolar nerve. All patients had metastases located in the posterior mandible. The primary tumours were ovarian, lung and breast in origin. Management included chemotherapy, radiotherapy and palliative care. Metastatic spread to the oral cavity is rare and is usually representative of wide‐spread oncological disease. Metastatic lesions should be included in the differential diagnosis of any patient presenting with paraesthesia of unknown aetiology. The dental practitioner may be the first clinician to identify such lesions following clinical examination and radiographic investigation.